Routing the opposition : social movements, public policy, and democracy - Meyer, David S.; Jenness, Valerie, 1963-; Ingram, Helen M., 1937- (Social movements, protest, and contention ;, 2005)
Capturing both successes and failures, Routing the Opposition focuses on strategies that transform social movements and guide the development of public policy, revealing what happens when the different organizational cultures of activists and public policy makers interact.